Value relevance of Other Comprehensive income and its Available-For-Sale Financial Instruments (AFS) and Revaluation Surplus of Property, Plant and Equipment (REV) components - Yousefinejad, Maryam; Azlina Ahmad,; Zaini Embong, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Studies on value relevance of Other Comprehensive Income (OCI) have thus far provided mixed evidences. Prior studies also found that fair value reporting has a significant impact on the value relevance of OCI. However, most studies on value relevance of OCI focused on developed countries where the capital market is more efficient. In these settings due to the existence of active market, fair valuation of assets may not pose a major problem. Therefore, more studies are needed to better understand the value relevance of such OCI especially in developing countries which have less efficient market. Thus, this study examined whether OCI and its components, Available-For-Sale Financial Instruments (AFS) andRevaluation Surplus of Property, Plant and Equipment (REV) are value relevant in Malaysia as a developing country. In order to fulfill these objectives, this study hypothesized that OCI and its components are associated with share price. These hypotheses were empirically tested using a sample of 1,419 firm years observations from 2011 to 2013, of firms listed on the Main Market of Bursa Malaysia. The results of Panel Analysis indicates that OCI and its components are value relevant. These results remain robust after additional analyses. This study provides additional evidence of value relevance of other comprehensive income in a developing country. The results indicate that the move towards a more comprehensive income reporting through the preparation of the Statement of Comprehensive Income results in more informative financial reporting.